Intrapsychic dimensions of addiction: the wearing down of help seeking capacities by cruel and tyrannical objects - English, Christine (2011)
Research had two aims: firstly, to explore the clinical observation that dependent drug users are often apparently unwilling, or are unable to reflect in any depth on experience, including thinking about mental states in self and other. Secondly, to consider the intrapsychic elements that exist alongside, and which may motivate drug addiction (including heavy and dependent alcohol use).